Two-phase flow in minichannels: hydrodynamics, pressure drop, and residence time distribution - Kulkarni, A. A.; Kalyani, Vishwanath S. (Industrial & Engineering Chemistry Research, 2009)
Two-phase flow in mini-channels (1 mm x 1.5 mm x 430 mm and 1.5 mm x 0.5 mm x 430 mm serpentine channel geometry) made in different materials (SS 316, PMMA and Teflon) was studied at different flow rate ratio (0.66, 1.0 and 1.56) of the two immiscible fluids. A dual syringe pump was used to pump the fluids (air-water and water-kerosene) through the channels. For characterization of the two phase flow, experiments were carried out to measure the slug size distribution and relevant hydrodynamic properties, pressure drop across a single serpentine unit (i.e., one sinusoidal unit that includes two 180 degrees return bends connected by a straight portion of 20 mm) and also the residence time distribution of water. In all the cases, the effect of material of fabrication on the hydrodynamics was significant. Apart from flow rates and flow rate ratio of the two fluids, the slug size distribution was seen to have a strong effect of the channel orientation (vertical, horizontal) and also the flow direction (up-flow and down-flow). In the RTD studies, the response curve observed at the end of the channel was significantly different than the published literature. The reasons for such observations are discussed in detail.

Telescoped sequence of exothermic and endothermic reactions in multistep flow synthesis - Sharma, Y.; Nikam, A. V.; Kulkarni, A. A. (Organic Process Research and Development, 2019)
A multistep sequential flow synthesis of isopropyl phenol is demonstrated, involving 4-step exothermic, endothermic, and temperature sensitive reactions such as nitration, reduction, diazotization, and high temperature hydrolysis. Nitration of cumene with fuming nitric acid produces 2- and 4-nitrocumene which are converted into respective cumidines by the hydrogenation using Pd/Ni catalyst in H-cube with gravity separation. Hydrolysis of in situ generated diazonium salts in the boiling acidic conditions is carried out using integration of flow and microwave-assisted synthesis. 58% of 4-isopropyl phenol was obtained. The sequential flow synthesis can be applied to synthesize other organic compounds involving this specific sequence of reactions.